2018
DOI: 10.1113/jp275327
|View full text |Cite
|
Sign up to set email alerts
|

The PHD1 oxygen sensor in health and disease

Abstract: The hypoxia-inducible factor (HIF) co-ordinates the adaptive transcriptional response to hypoxia in metazoan cells. The hypoxic sensitivity of HIF is conferred by a family of oxygen-sensing enzymes termed HIF hydroxylases. This family consists of three prolyl hydroxylases (PHD1-3) and a single asparagine hydroxylase termed factor inhibiting HIF (FIH). It has recently become clear that HIF hydroxylases are functionally non-redundant and have discrete but overlapping physiological roles. Furthermore, altered abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 111 publications
(140 reference statements)
0
19
0
Order By: Relevance
“…Historically, a variety of acute and chronic O 2 ‐sensing mechanisms have been proposed. These include increases, or paradoxically decreases, in reactive oxygen species (ROS), activation or inactivation of metabolites, for example, nitric oxide, prostanoids, etc, AMP‐activated protein kinase, ion channels, Na,K ATPase, haeme and other proteins and the hypoxia inducible factors …”
Section: Introductionmentioning
confidence: 99%
“…Historically, a variety of acute and chronic O 2 ‐sensing mechanisms have been proposed. These include increases, or paradoxically decreases, in reactive oxygen species (ROS), activation or inactivation of metabolites, for example, nitric oxide, prostanoids, etc, AMP‐activated protein kinase, ion channels, Na,K ATPase, haeme and other proteins and the hypoxia inducible factors …”
Section: Introductionmentioning
confidence: 99%
“…Further studies of transgenic animals have provided intriguing insights into the role of individual PHD enzymes during the development of chronic diseases. For example, PHD1-deficient mice are protected against colitis or liver pathologies such as biliary fibrosis or ischemia/reperfusion injury [21,22,23,24,25].…”
Section: Hif Hydroxylationmentioning
confidence: 99%
“…In general, HIF-P4H-2 has been reported to be quite ubiquitously expressed, being the predominant HIF-P4H isoform in most tissues studied, for example in the heart, brain, liver, skeletal muscle and kidney, while it was detected only at low levels in the lung [ 15 , 16 , 17 ]. HIF-P4H-1 has been postulated to be the only isoform expressed in the testes [ 15 , 18 ], although another study demonstrated an abundance of all three isoforms in this tissue [ 19 ]. Highest HIF-P4H-3 expression has been detected in the heart [ 15 ] and HIF-P4H-3 seems to be particularly strongly expressed in epithelial cells of various tissues [ 19 ].…”
Section: Introductionmentioning
confidence: 99%